American Cocker Spaniel Chronic Hepatitis in Japan. (19th June 2013) - Kanemoto, H.; Sakai, M.; Sakamoto, Y.; Spee, B.; van den, T.S.G.A.M.; Schotanus, B.A.; Ohno, K.; Rothuizen, J.
<x xml:space="preserve">Abstract</x> Background American Cocker Spaniels are predisposed to chronic hepatitis. Objective To describe the clinical and histological features of chronic hepatitis in Japanese American Cocker Spaniels. Animals Thirteen cases examined from 2003 to 2009. Methods Retrospective study. Medical records were searched for American Cocker Spaniels with chronic liver diseases. History, physical examination, clinicopathologic features, hepatic ultrasonographic findings, hepatic histopathology, and immunohistochemistry were evaluated. Results The median age was 4.6 (1.9–10.7) years. Clinical signs included inappetence (11/13), ascites (11/13), lethargy (9/13), diarrhea (7/13), and melena (2/13). Only 1/13 dogs was jaundiced. Clinicopathological abnormalities were increased liver enzymes (gamma‐glutamyl transpeptidase: 9/12, aspartate aminotransferase: 7/10, alanine aminotransferase: 6/13, alkaline phosphatase: 6/13), increased total serum bile acid concentrations (10/12), and hypoalbuminemia (10/13). The liver had an irregular surface in all dogs and acquired portosystemic collaterals were verified in 11/13 dogs by abdominal ultrasound (2), laparoscopy (4), or both (5). Liver histology revealed severe fibrosis and cirrhosis in all cases, subdivided in lobular dissecting hepatitis (7), periportal fibrosis (1), micronodular cirrhosis (3), and macronocular cirrhosis (2). Inflammatory activity was low to mild. Immunohistochemical stains showed ductular proliferation. The median survival time was 913 (range: 63–1981) days. Conclusion and Clinical Importance Hepatitis in Japanese American Cocker Spaniels is clinically silent until an advanced stage and is associated with severe hepatic fibrosis leading to cirrhosis, extensive ductular/putative hepatic progenitor cell proliferation, portal hypertension, and acquired portosystemic collateral shunting, but relatively long survival times. Lobular dissecting hepatitis seems more prevalent than in previously reported cases from other countries.